Incidence of new morbidity based on Functional Status Scale in children on discharge from pediatric intensive care unit of a developing country: A single-center observational study - Anwarul Haque; Shoaib Bhatti; Saira A Ahmed; I Zafar Muhammad (Wolters Kluwer Medknow Publications, 2022)
Background: Recently, short-term outcome among survival of children from pediatric intensive care unit (PICU) is assessed using the Functional Status Scale (FSS). New morbidity was defined as an increase in FSS score of ≥3 points from baseline to discharge from PICU. The objective of the study was to assess the incidence of newly acquired morbidity based on FSS in children on discharge from PICU. Subjects and Methods: A cross-sectional retrospective study was conducted on children (1 month-15 years) who were discharged alive from PICU from November 2021 to January 2022. The functional status was evaluated using FSS on the 1st day of admission and discharge from PICU to measure newly acquired morbidity. Results: Of a total of 200 patients, 155 patients were included in the study. The mean age was 3.79 ± 3.76 years, and 63.2% (98) were male. The mean PRISM score was 12.99 ± 5.22. The most common diagnostic categories were acute respiratory illnesses (41.3%) and infectious diseases (23.2%). The median FSS was 6.00 on admission, and the mean FSS on discharge was 7.02 ± 2.22. The incidence of morbidity was 12.2% (19/155). Young children and children with neurological diseases were highly associated with new morbidity in critically ill children on discharge from PICU. However, there was no statistical significance. The mortality rate was 11.5% during the same period. Conclusions: The incidence of new morbidity in critically ill pediatric patients at PICU discharge was 12.2%. Young age and children with neurological diseases were at high risk for new morbidity. Most of the patients (>94%) were discharged with good functional status.